Barrier to online repayment : A case of PTPTN loan / Mohd Adib Mohd Salleh @ Salih - Mohd Salleh @ Salih, Mohd Adib (2005)
PTPTN known as National Education Higher Fund Corporation has been considered as the traditional approach for supporting tertiary education in Malaysia. PTPTN provides educational loans for tertiary education level in Malaysia for qualified applicants and managing repayment process for ex-students at the same time. The National Education Higher Fund Corporation (PTPTN) has a deficit of RM7 billion. PTPTN ran out of funds in 2003 and had to borrow RM2 billion from the EPF to keep the tap going due to the small number of PTPTN borrowers who repay their loans. PTPTN borrowers refuse to repay and settle their loans because of some barrier occur during online transaction and not satisfied with the current requirements for the transaction process. Online payment is a new technology that will make our life less complicated with less money presence a fast and a secure payment transaction could be made based on a system that has been programmed to transfer fund from one account to another recipient account. This method is one of the best methods since it is easy accessible, saves time and reduce expenses. This research will reveal the barrier towards the current online repayment system of PTPTN loan. A total of 200 samples of PTPTN borrowers were chosen around Klang Valley but only 115 respondents gave feedback by answering the distributed questionnaires. Statistical analysis was carried out in order to obtain the intention results required by the objective that have been stated in the early stages of the research. A test was carried out on variables that are important in determining its significance to the hypothesis statement. Based on the findings and results, all objectives were successfully achieved with findings such as the most influence barrier towards the current online repayment system of PTPTN loan.